1976
DOI: 10.1085/jgp.67.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Proton transport by phosphate diffusion--a mechanism of facilitated CO2 transfer.

Abstract: A B S X R A C X We have measured CO2 fluxes across phosphate solutions at different carbonic anhydrase concentrations, bicarbonate concentration gradients, phosphate concentrations, and mobilities. Temperature was 22-25"C, the pH of the phosphate solutions was 7.0-7.3. We found that under physiological conditions of pH and pCO~ a facilitated diffusion of CO2 occurs in addition to free diffusion when (a) sufficient carbonic anhydrase is present, and (b) a concentration gradient of HCO3-is established along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…An analogous mechanism has been proposed by us (7)(8)(9) for facilitated CO2 diffusion in buffer solutions: a facilitated CO2 flux is brought about by identical fluxes of HCO3 and protons. Whereas the former is based on free diffusion of HCOj the mechanism responsible for the latter is a facilitated proton diffusion by translational buffer diffusion:…”
supporting
confidence: 58%
See 1 more Smart Citation
“…An analogous mechanism has been proposed by us (7)(8)(9) for facilitated CO2 diffusion in buffer solutions: a facilitated CO2 flux is brought about by identical fluxes of HCO3 and protons. Whereas the former is based on free diffusion of HCOj the mechanism responsible for the latter is a facilitated proton diffusion by translational buffer diffusion:…”
supporting
confidence: 58%
“…HC -H20 CO This mechanism of facilitated proton transport by translational protein diffusion has been found to be solely responsible for proton transport in phosphate, myoglobin, and albumin (30 g/dl) solutions (7)(8)(9). It does not,' however, appear to be the sole mechanism of proton transport in earthworm Hb (EW-Hb) solutions.…”
mentioning
confidence: 99%
“…gradient originates from anaerobic production of lactic acid (Brockhaus et al 1993). Maintained extracellular pH gradients have been suggested to be due to increased anaerobic metabolism also in other mammalian CNS preparations, both in vitro and in vivo (for references, see Hansen, 1985;Chesler, 1990 Longmuir, Forster & Woo, 1966;Gros, Moll, Hoppe & Gros, 1976) or retarded by macromolecular structures (e.g. Gros & Moll, 1971), or both.…”
Section: Localization Of Chemosensitive Structuresmentioning
confidence: 99%
“…However, using an in situ preparation in a pithed, artificially ventilated whole dogfish, Swenson and Maren (Swenson and Maren, 1984) reported that CA inhibition reduced rectal gland secretion. They speculated that the normal role of CA is to facilitate the diffusive excretion of CO 2 from the metabolically active gland cells, in accord with the pioneering work of Gros in muscle tissue (Gros et al, 1976;Gros, 1991), but their results may have been confounded by the loss of neural control and depressed circulation in this preparation, as well as systemic effects of CA inhibition.…”
Section: Introductionmentioning
confidence: 93%
“…However, there is one important difference: Swenson and Maren interpreted CA as acting in the intracellular compartment as a true facilitator of CO 2 diffusion [i.e. via the co-diffusion of HCO 3 -and buffered H + , which is the model of Gros and coworkers (Gros et al, 1976;Gros, 1991)], whereas we propose that CA serves to catalyze the CO 2 hydration reaction in the extracellular compartment, so as to maintain the P CO 2 gradient from cell to blood/perfusate. This interpretation is in accord with Lacy's original localization of CA (Lacy, 1983).…”
Section: The Role Of Carbonic Anhydrase In Rectal Gland Functionmentioning
confidence: 99%